PRELIMINARY ESTIMATION ON AIR POLLUTION LOAD OVER BOGOR CITY TOWARDS DEVELOPMENT OF CLEAN AIR ACTION PLAN - Didin Agustian Permadi; Mila Dirgawati; Agung Ghani Kramawijaya; Widi Hermawan (Pusat Standardisasi Instrumen Kualitas Lingkungan Hidup Laboratorium Lingkungan (P3KLL), 2020)
Emission inventory (EI) data are crucial to provide source apportionment and relative strength of various air pollutant sources in a city. The process of EI compilation can be either bottom-up or top-down, which depends on data availability and other resources. For a city like Bogor, known as a buffer zone of the capital of the Republic of Indonesia, these EI data are now available only for greenhouse gases (GHGs) but not for the air pollutants. Therefore, a top-down EI was designed and implemented for the city in the base year of 2016. Note that the sources of activity data were compiled from the previously arranged GHGs EI database as well as some other data gathered from the local authority. We adopted the EI framework of the Atmospheric Brown Cloud Emission Inventory Manual spreadsheet for the compilation. We included SO2, CO, NO2, PM10, PM2.5, NMVOC, and PM components (black carbon and organic carbon). Point sources, area sources, as well as mobile sources, were considered in the emission estimation. The latter species were included as they are known as strong short-lived climate-forcing pollutants (SLCPs). On-road transport contributed significantly to SO2, NMVOC, and PM2.5, with a portion of 60-86% of the total emission. Industrial combustion sources dominated the shares to the total emissions of NOx (91%) and CO (92%). Based on this baseline information, we then proposed the source wise clean air action plan for the city in order to reduce the emission. A more accurate and up to date EI database should be done through a survey to get local representative activity data and to be compiled on a regular basis.